Improvement of registration accuracy in accelerated partial breast irradiation using the point‐based rigid‐body registration algorithm for patients with implanted fiducial markers. Issue 4 (26th March 2015) - Inoue, Minoru; Yoshimura, Michio; Sato, Sayaka; Nakamura, Mitsuhiro; Yamada, Masahiro; Hirata, Kimiko; Sasaki, Makoto; Fujimoto, Takahiro; Ogura, Masakazu; Hiraoka, Masahiro
Abstract : Purpose: To investigate image‐registration errors when using fiducial markers with a manual method and the point‐based rigid‐body registration (PRBR) algorithm in accelerated partial breast irradiation (APBI) patients, with accompanying fiducial deviations. Methods: Twenty‐two consecutive patients were enrolled in a prospective trial examining 10‐fraction APBI. Titanium clips were implanted intraoperatively around the seroma in all patients. For image‐registration, the positions of the clips in daily kV x‐ray images were matched to those in the planning digitally reconstructed radiographs. Fiducial and gravity registration errors (FREs and GREs, respectively), representing resulting misalignments of the edge and center of the target, respectively, were compared between the manual and algorithm‐based methods. Results: In total, 218 fractions were evaluated. Although the mean FRE/GRE values for the manual and algorithm‐based methods were within 3 mm (2.3/1.7 and 1.3/0.4 mm, respectively), the percentages of fractions where FRE/GRE exceeded 3 mm using the manual and algorithm‐based methods were 18.8%/7.3% and 0%/0%, respectively. Manual registration resulted in 18.6% of patients with fractions of FRE/GRE exceeding 5 mm. The patients with larger clip deviation had significantly more fractions showing large FRE/GRE using manual registration. Conclusions: For image‐registration using fiducial markers in APBI, the manual registration results in more fractions with considerable registration error due to loss of fiducial objectivity resulting from their deviation. The authors recommend the PRBR algorithm as a safe and effective strategy for accurate, image‐guided registration and PTV margin reduction.